Relationship Between Change in Serum Uric Acid and Ischemic Stroke in Chinese Hypertensive Patients - Tan, Qiu-hong; Liu, Lin; Huang, Yu-qing; Yu, Yu-ling; Huang, Jia-yi; Chen, Chao-lei; Tang, Song-tao; Feng, Ying-qing (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background: Limited studies focused on the association between serum uric acid (SUA) change with ischemic stroke, and their results remain controversial. The aim of the present study was to investigate the relationship between change in SUA with ischemic stroke among hypertensive patients. Method: This was a retrospective cohort study. We recruited adult hypertensive patients who had two consecutive measurements of SUA levels from 2013 to 2014, and reported no history of stroke. Change in SUA was assessed as SUA concentration measured in 2014 minus SUA concentration in 2013. Multivariable Cox proportional hazards models were used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs). The Kaplan-Meier analysis and Log-rank test were performed to quantify the difference in cumulative event rate. Additionally, subgroup analysis and interaction tests were conducted to investigate heterogeneity. Results: A total of 4628 hypertensive patients were included, and 93 cases of ischemic stroke occurred during the mean follow-up time of 3.14 years. Participants were categorized into three groups according to their SUA change tertiles [low (SUA decrease substantially) :< -32.6umol/L; middle (SUA stable): ≥ -32.6 umol/L, < 40.2 umol/L; high (SUA increase substantially): ≥ 40.2 umol/L]. In the fully-adjusted model, setting SUA stable group as reference, participants in the SUA increase substantially group had a significant elevated risk of ischemic stroke [HR(95%CI), 1.76 (1.01, 3.06), P=0.0451], but for the SUA decrease substantially group, the hazard effect was insignificant [HR(95%CI), 1.31 (0.75, 2.28), p=0.3353]. Age played an interactive role in the relationship of SUA change and ischemic stroke. Younger participants (age <65 years) tended to have higher risk of ischemic stroke when SUA increase substantially. Conclusion: SUA increase substantially was significantly correlated with elevated risk of ischemic stroke among patients with hypertension.